A BJT-based temperature sensor using two sub-OPAMPs Chopper ripple reduction technique with inaccuracy of ±0.25 °C (3σ) from −45 °C to 85 °C. (May 2022) - Guo, Qiansong; Ma, Xia; Xiao, Zhiming; Hu, Yi; Feng, Jingbin; Wang, Meiyu; Hu, Weibo
Abstract: This paper presents a BJT-based temperature sensor inaccuracy of ±0.25 °C (3σ). To handle noises in AFE and ADCs, two modified techniques are put forward, respectively. One technique utilized in the analog front end is modified choppers with two sub-OPAMPs. Two sub-OPAMPs chopped under two non-overlapped clocks with 90-degree phase difference are used to suppress the chopper ripple while removing low frequency noises. To achieve an accurate digitization, a zoom ADC which combines SAR coarse conversion and Sigma-Delta fine conversion is applied for its high resolution and energy-efficiency. One-time offset calibration is used in the OPAMP of the 1st integrator to ensure the good integrator performance. After one-point trimming, the proposed design achieves inaccuracy of ±0.25 °C (3σ) from −45 °C to +85 °C. It occupies 0.18 mm 2 in a 110 nm CMOS, and draws 12.3 μA from a 3 V supply, with a conversion time of either 4 ms or 8 ms.